2018
DOI: 10.1021/acs.jced.7b00887
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Equilibrium of Water + 2-Methoxyphenol + Methyl Isobutyl Ketone and Water + 1,2-Benzenediol + Methyl Isobutyl Ketone at 303.15 K and 328.15 K

Abstract: Liquid–liquid equilibrium (LLE) experiments for the systems water + 2-methoxyphenol + MIBK and water + 1,2-benzenediol + MIBK were carried out at 303.15 and 328.15 K according to a procedure allowing the measurement of both the composition of the phases in equilibrium and their relative amounts. Binary LLE data of subsystems water + MIBK and water + 2-methoxyphenol were also measured, as was the solubility of 1,2-benzenediol in water. The experimental data were modeled using the NRTL activity coefficient model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“… a T b PC‑SAFT is the boiling temperature in K at 101.3 kPa, w s w,PC‑SAFT and w s s,PC‑SAFT is the mass fraction of solvent in the aqueous and solvent phase, respectively, log K phe PC‑SAFT is the partition coefficients at infinite dilution of 2-phenylethanol in the water-solvent system, all of them at 303.15 K and 101.3 kPa, and HSE is the recommendation of solvent use from health, safety, and environmental indicators. In parentheses are reported experimental values. b Retrieved from Aspen Plus V.12. c From Montesantos et al d From Raal and Brouckaert e From Stephenson …”
Section: Resultsmentioning
confidence: 99%
“… a T b PC‑SAFT is the boiling temperature in K at 101.3 kPa, w s w,PC‑SAFT and w s s,PC‑SAFT is the mass fraction of solvent in the aqueous and solvent phase, respectively, log K phe PC‑SAFT is the partition coefficients at infinite dilution of 2-phenylethanol in the water-solvent system, all of them at 303.15 K and 101.3 kPa, and HSE is the recommendation of solvent use from health, safety, and environmental indicators. In parentheses are reported experimental values. b Retrieved from Aspen Plus V.12. c From Montesantos et al d From Raal and Brouckaert e From Stephenson …”
Section: Resultsmentioning
confidence: 99%
“…Suitable solvents must have not only good extraction performance but also have appropriate properties . For example, methyl isobutyl ketone (MIBK) and cyclohexanone (CYC) have good extraction performance in an aqueous system and were widely used in industry . In recent years, many studies have been conducted on the literature with the LLE data of MIBK and CYC in water systems.…”
Section: Introductionmentioning
confidence: 99%
“…12 For example, methyl isobutyl ketone (MIBK) and cyclohexanone (CYC) have good extraction performance in an aqueous system and were widely used in industry. 13 In recent years, many studies have been conducted on the literature with the LLE data of MIBK and CYC in water systems. The LLE data of the system (CYC + water + phenol) from 298.15 to 323.15 K in 101.3 kPa were explored by Cai et al 14 Dong et al 15 investigated the (water + furfuryl alcohol + MIBK) system at 298.2 K and 101.3 kPa.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 25 applied n-butyl acetate to separate pyrocatechol and reported LLE data for n-butyl acetate + pyrocatechol + water. The phase equilibrium behavior of (methyl isobutyl ketone + benzene-1,2-diol + water) was investigated by Montesantos et al 26 Solvents mentioned above have high solubilities in the aqueous phase larger than 1%. Separation and recovery of the extraction solvent from water require more energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al applied n -butyl acetate to separate pyrocatechol and reported LLE data for n -butyl acetate + pyrocatechol + water. The phase equilibrium behavior of (methyl isobutyl ketone + benzene-1,2-diol + water) was investigated by Montesantos et al…”
Section: Introductionmentioning
confidence: 99%